Hydrogen embrittlement of cold drawn prestressing steels: the role of the die inlet angle - Toribio, J.; Lorenzo, M.; Vergara, D.; Kharin, V. (Фізико-хімічна механіка матеріалів, 2013)
Cold-drawn prestressing steel wires are susceptible to hydrogen embrittlement (HE) in aggressive environments, and residual stress-strain states generated in wires by the drawing process play the key role there. Correspondingly, alterations of the stress-strain fields due to peculiarities of the drawing procedure affect the serviceability of wires under HE. On the basis of performed numerical simulations of the process of cold drawing with the use of different drawing dies, the paper addresses the effect of the inlet angle of the die on residual stress-strain fields in wires, and derives their consequences for wires hydrogenation and their susceptibility to HE. The reduction of the die inlet angle is shown to be beneficial for the wires performance.